2013
DOI: 10.1097/igc.0b013e318280f3bc
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cervical Cancer Screening and Triage Using an mRNA Human Papillomavirus Assay and Visual Inspection

Abstract: The specificity of the APTIMA assay along with high sensitivity is an advantage for primary screening. Follow-up evaluation will be important to determine the true impact of potential undertreatment in the screening algorithm. Self-sampling applications are explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 31 publications
2
28
0
1
Order By: Relevance
“…Our findings are fully in line with those of other studies that compared the clinical performance of the Aptima HPV assay with that of a variety of commercially available HPV assays for ASC-US/low-grade squamous intraepithelial lesion triage or primary screening (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The current study adds because it addresses all aspects of the guidelines, including intralaboratory reproducibility over time and interlaboratory agreement of the Aptima HPV assay.…”
Section: Discussionsupporting
confidence: 79%
“…Our findings are fully in line with those of other studies that compared the clinical performance of the Aptima HPV assay with that of a variety of commercially available HPV assays for ASC-US/low-grade squamous intraepithelial lesion triage or primary screening (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The current study adds because it addresses all aspects of the guidelines, including intralaboratory reproducibility over time and interlaboratory agreement of the Aptima HPV assay.…”
Section: Discussionsupporting
confidence: 79%
“…The aforementioned meta-analysis demonstrated that the sensitivity and specificity of HPV testing are similar on self-as on cliniciantaken samples when validated PCR tests are used but not when signal amplification-based HPV assays are applied (12). The conclusions of this meta-analysis remain unchanged after the addition of recently published studies (12,(14)(15)(16). The pooled relative sensitivity and specificity of 19 studies using HC2 (Qiagen) in self-versus clinician-collected samples were 0.86 (95% CI, 0.82-0.91) and 0.96 (95% CI, 0.93-0.98), respectively (see Fig.…”
mentioning
confidence: 84%
“…Adjunctive testing to cytology, however, leads to reduced combined sensitivity. The AHPV test has also been suggested as the primary cervical cancer screening test in a few studies (10,13,14). HPV DNA screening, with certain requirements, has already been identified as an alternative option for primary cervical cancer screening (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…However, the poor sensitivity of cytology demands the development of more-accurate screening schemes. Strategies for the improvement of early diagnosis of CIN2ϩ cases have been assessed for the AHPV assay based on the primary screening test being cytology (10)(11)(12)(13)(14)(15)(16)(17)(18). Adjunctive testing to cytology, however, leads to reduced combined sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation